Recent insight into intermediate filament structure. (February 2021) - Eldirany, Sherif A.; Lomakin, Ivan B.; Ho, Minh; Bunick, Christopher G.
Abstract: Intermediate filaments (IFs) are key players in multiple cellular processes throughout human tissues. Their biochemical and structural properties are important for understanding filament assembly mechanisms, for interactions between IFs and binding partners, and for developing pharmacological agents that target IFs. IF proteins share a conserved coiled-coil central-rod domain flanked by variable N-terminal 'head' and C-terminal 'tail' domains. There have been several recent advances in our understanding of IF structure from the study of keratins, glial fibrillary acidic protein, and lamin. These include discoveries of (i) a knob–pocket tetramer assembly mechanism in coil 1B; (ii) a lamin-specific coil 1B insert providing a one-half superhelix turn; (iii) helical, yet flexible, linkers within the rod domain; and (iv) the identification of coil 2B residues required for mature filament assembly. Furthermore, the head and tail domains of some IFs contain low-complexity aromatic-rich kinked segments, and structures of IFs with binding partners show electrostatic surfaces are a major contributor to complex formation. These new data advance the connection between IF structure, pathologic mutations, and clinical diseases in humans. Graphical abstract: Image 1 Highlights: Intermediate filament domain structures provide insight into assembly mechanisms. Heads and tails may contain low-complexity aromatic-rich kinked segments. Electrostatic surfaces help intermediate filaments bind partner proteins. The genotype and structurotype contribute to the clinic phenotype in human diseases.